MULTIDISCIPLINARY APPROACH TO CHRONIC CONSTIPATION ASSOCIATED WITH FECAL INCONTINENCE IN CHILDREN - Claudia Olaru; Smaranda Diaconescu; Valeriu V. Lupu; Nicoleta Gimiga; Gabriela Paduraru; Ancuta Ignat; Radian A. Olaru; Vasile Drug; Marin Burlea (Amaltea Medical Publishing House, 2015)
Constipation is a common symptom in clinical practice. Defi nition include abnormal transit diffi culty during defecation and abnormal stool consistency. Limited diagnostic methods and the many diseases that lead to symptoms, leading to more cases of drug resistance. Treatment includes dietary and behavioral approaches, pharmacological therapy and surgery in carefully selected cases. Surgery is recommended in patients with severe constipation resistant to conservative treatment. Confi rmation of indication for surgical treatment requires colonic transit studies, defecation function and conducting anorectal manometry. Therefore, a close collaboration between pediatric gastroenterologists and surgeon pediatricians is essential for the careful preoperative evaluation and gastrointestinal function. Postoperative complications include intestinal obstruction, abdominal pain, flatulence and diarrhea. The effectiveness of surgery and prevalence of postoperative complications are determined by a careful preoperative evaluation of the gastrointestinal function.